2016
DOI: 10.1098/rspb.2016.0164
|View full text |Cite
|
Sign up to set email alerts
|

Superior discrimination for hue than for saturation and an explanation in terms of correlated neural noise

Abstract: The precision of human colour discrimination depends on the region of colour space in which measurements are made and on the direction in which the compared colours-the discriminanda-differ. Working in a MacLeod-Boynton chromaticity diagram scaled so that thresholds at the white point were equal for the two axes, we made measurements at reference points lying on lines that passed at 458 or 2458 through the white point. At a given reference chromaticity, we measured thresholds either for saturation (i.e. for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
(72 reference statements)
1
14
0
Order By: Relevance
“…For example, Krauskopf and Gegenfurtner (1992) found that detection thresholds for very small targets against large uniform chromatic backgrounds are constant and symmetric in the red and green directions for varying background chromaticities, while thresholds increase symmetrically in the blue and yellow directions for increasing levels of background S-cone stimulation. Another asymmetry that has been observed in chromatic discrimination experiments is between changes in hue and changes in saturation, with higher thresholds reported for the latter (Danilova & Mollon, 2016; Elliott, Werner, & Webster, 2012; Krauskopf & Gegenfurtner, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Krauskopf and Gegenfurtner (1992) found that detection thresholds for very small targets against large uniform chromatic backgrounds are constant and symmetric in the red and green directions for varying background chromaticities, while thresholds increase symmetrically in the blue and yellow directions for increasing levels of background S-cone stimulation. Another asymmetry that has been observed in chromatic discrimination experiments is between changes in hue and changes in saturation, with higher thresholds reported for the latter (Danilova & Mollon, 2016; Elliott, Werner, & Webster, 2012; Krauskopf & Gegenfurtner, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the color difference, hue shifts were reported to provide more specific information about the color quality of the artwork. Because hue discrimination thresholds are lower than saturation discrimination thresholds (Danilova and Mollon 2016), hue shift calculations were added to capture the most essential dimension of the color quality of the artwork under optimized lighting conditions. Color (ΔE 00 ) and hue (ΔH′) differences were calculated using CIE 1976 (L*, a*, b*) and CIEDE2000 color difference formulae (CIE 2004b).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the third approach is to employ a multiplicative rather than an additive noise model. The precision of perceptual representations is often the highest at the current adaptation point [3638]. This observation can be incorporated in the model by assuming that along each perceptual dimension noise scales as a function of test distance from the target.…”
Section: Discussionmentioning
confidence: 99%